Destination Cileuweung: Crafting a Comprehensive Masterplan for Tourism Development in Cileuweung Village, Cimahi City - Syaodih, Ernady; Damayanti, Verry; Fardani, Irland; Widagdo, Rama Arianto; Burhanudin, Hani; Wildan, Fachri Hilmansyah; Djiwangsa, Farell Hakeem Ihza; Mufid, Sa'dan; Napitupulu, Bertha Anissa Maisarah (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2026)
Abstract. Cileuweung Village in Cimahi City has the potential for educational tourism based on cattle farming and dairy products; unfortunately, it has not been optimally managed. This study aims to develop a master plan for the development of a community-based tourism village by involving the community and local government. Through field observation, literature study, and Focus Group Discussion (FGD) with the participation of local residents, we gather data to help understand more about the village and find the right direction for its development. The results of the study show that Cileuweung Village has tourism potential in the form of beautiful natural scenery, a cool climate, camping areas, cattle farms, plantations, small dairy processing industries, wood waste crafts, and local wisdom. The community and government are very enthusiastic about developing a tourist village, but face obstacles in the form of limited tourism infrastructure, human resource readiness, and minimal promotion. The master plan developed includes two zones with ten key functional areas. The participatory approach is expected to actualize sustainable tourism village development, improve community welfare, and preserve local culture and the environment